1993
DOI: 10.1093/eurheartj/14.6.770
|View full text |Cite
|
Sign up to set email alerts
|

Element concentrations (selenium, copper, zinc, iron, magnesium, potassium, phosphorous) in heart tissue of patients with coronary heart disease correlated with physiological parameters of the heart

Abstract: The element concentrations (Cu, Zn, Se, Fe, K, Mg, P) of heart tissue taken from patients with coronary heart disease during bypass surgery were measured and related to physiological parameters of the heart. There was no relationship between the element concentrations and the number of vessels stenosed, the occurrence of myocardial infarction or classification according to the NYHA. When the element concentrations of the heart were related with parameters characterizing cardiac output, such as ejection fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 0 publications
2
26
1
1
Order By: Relevance
“…Cardiac zinc content correlates positively with ejection fraction (EF) in humans (18), and zinc supplementation to cardioplegic solution protects against the loss of systolic function and enhances diastolic function during and after ischemia-reperfusion injury (23)(24)(25). It has been suggested that zinc combats oxidative stress associated with ischemia-reperfusion and diabetes in part by enhancing the capacity of the zinc-binding protein metallothionein (15), which shields against reactive oxygen species (13, 23-25, 27, 36).…”
mentioning
confidence: 99%
“…Cardiac zinc content correlates positively with ejection fraction (EF) in humans (18), and zinc supplementation to cardioplegic solution protects against the loss of systolic function and enhances diastolic function during and after ischemia-reperfusion injury (23)(24)(25). It has been suggested that zinc combats oxidative stress associated with ischemia-reperfusion and diabetes in part by enhancing the capacity of the zinc-binding protein metallothionein (15), which shields against reactive oxygen species (13, 23-25, 27, 36).…”
mentioning
confidence: 99%
“…Also, in such patients, the myocardial tissue concentrations of these micronutrients showed positive correlations with cardiac output parameters [50,51] As stated before, arterial hypertension is accompanied by changes in zinc metabolism and its redistribution that may lead, at least, to zinc deficiency [52]. In turn, zinc deficiency may impair myocardial compensatory and reconstructive processes on increased left ventricular load and finally lead to left ventricular failure.…”
Section: Discussionmentioning
confidence: 66%
“…Oster et al (89) found a positive correlation between cardiac output and copper in heart tissue of patients with coronary heart disease (in addition to the similar correlation with selenium noted in Subheading 3). Copper deficient rats resemble those deficient in selenium in some aspects of selenium metabolism (71).…”
Section: Ischemic Heart Disease Resembles Copper Deficiencymentioning
confidence: 62%